Influence of digital marketing, word of mouth, and price perceptions on purchasing decisions product uses home credit - Makatita, Ilham Ramadhana; Supriyono, Supriyono (Jurnal Ekonomi, 2024)
This research was conducted to know the influence of digital marketing, word of mouth, and price perceptions on product purchasing decisions using Home Credit. This research uses a population of Home Credit consumers, while the sampling technique used is purposive sampling. The number of samples in this research was 112 consumers. The technique used in data collection is a questionnaire. Data from the results of distributing questionnaires was processed using Partial Least Square (PLS). The results obtained in this research are that digital marketing contributes to the decision to purchase products using Home Credit, word of mouth contributes to the decision to purchase products using Home Credit, and price perception contributes to the decision to purchase products using Home Credit.